A aposentadoria por idade no Direito Brasileiro - Vargas, Eliana Fiorini (2005)
This work aims the analysis of the evolution of social protection, in the world and in Brazil and, in this context, the study of the benefit retirement per age. In the international arena, it is underscored the creation of the social welfare attributed to the Chancellor Otto von Bismarck, in Germany, and, to the innovations brought by Lord William Beveridge, in England. Finally, the Convention n. 102 of the International Labour Organization known as the \"minimum standards\" of social security is analyzed. In the national arena, the historical analysis starts by the Elói Chaves Law, considered the official landmark of social welfare in Brazil; passes through the creation of the Reserves (Caixas) and the Institutes of Retirement and Pensions, the unification in 1966 with the creation of the Social Welfare National Institute (INPS), up to the Republic Constitution of 1988, that brought several advancements to the social security. It is important to reckon that the social security is formed by welfare, social assistance and healthcare. Among the risks protected by the welfare system, this work studies the old age. The aging of population is a global issue that demands a change in behavior and in the delivery of services. While the birth rate decreases, life expectancy increases. But, guaranteeing quality life to people remains a challenge both to the developed and developing countries. The aging of population affects social welfare directly. The benefit that protects the risk of old age is analyzed in the second part of this work. The instrument for analyzing the benefit is the main rule. The differences between retirement per age in men and women and the urban and rural workers are analyzed. The study was the result of doctrinarian research, national and foreign, jurisprudence and legislation. In these days, a social welfare system without retirement per age is unthinkable. The old age risk must be protected and the retirement per age is the instrument of this protection.